Cyclodextrin Oligomers - Sliwa, Wanda; Girek, Tomasz; Koziol, Jacek J. (Current Organic Chemistry, 2004)
Selected examples of cyclodextrin (CD) oligomers have been presented, describing their syntheses, physicochemical properties and application possibilities. The first part of the review concerns CD dimers, the second one deals with CD trimers and tetramers. The references are cited mainly of reports that appeared during the years 2001-2003.
Keywords: cd trimers